Critical evaluation of the sustainabile development principles within the fashion business model components for early-stage company - Vynogradova, Olena; Pysar, Nadiia; Drokina, Nina; Lytvynova, Olga; Sovershenna, Iryna (Technology audit and production reserves, 2021)
The object of research is the processes of interaction of business model components for the enterprise in the fashion industry at an early stage of its life cycle, which are subject to the principles of sustainable development and distinguish the business model from the model of «fast fashion». One of the most problematic places is to determine the actual components of the business model of the enterprise of the fashion industry, working on the principles of sustainable development, rather than those that are only declared by the company itself. And also used as a tool for promotion without the actual implementation of these tools. In addition, it is important not only to establish a minimum list of such tools, but also to establish their relationship. The study used methods of detailed analysis of the current state of the problem, based on information retrieval with extensive use of computers. Methods of empirical research (observation, comparison), method of synthesis and structural-genetic method (extraction from the complex phenomenon of such elements which considerably influence other parties of object of research, in a investigated case of tools of sustainable development) were also used. Various sources of information, databases EBSCO, ResearchGate, Jstor, secondary sources of information, company websites, analytical reports were used. As well as primary sources – interviews with representatives of fashion industry companies that implement «sustainable» practices in business processes at their enterprises (for example, Ze Kout LLC, Kyiv, Ukraine). The scientific and practical value of the study is that the business activities of modern companies must be consistent with the goals of sustainable development stated by the UN. And development – to involve its consumers not only in the promotion, evaluation or promotion of existing products, but also in the creation of quality products based on the principles of sustainable development. This provides an opportunity to renew the cooperation of companies, update the mission, goals, and vision of business development at high quality standards of sustainable economic development. This allows to reasonably approach the construction of business on the principles of sustainable development and obtain economic effects from the introduction into production of the principles of sustainable development. In particular, product quality can be improved.